Najdłuższa polska autobiografia - fenomen twórczości Joanny Chmielewskiej = The longest Polish autobiography - the phenomena of Joanna Chmielewska`s works - Gazdecka, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article emphasized the presence and significance of the longest Polish autobiography. It was supposed to make you wonder if only the aesthetic functions of literature are the only ones worth attention today? Can contemporary literature influence the shaping of society?
Keywords: Chmielewska, Joanna (1932-2013); biografia; autobiografizm wyrafinowany; podwójna biografia; feminizm; PRL; biography; sophisticated autobiography; double biography; feminism